WATER LOSSES DETECTION IN NETWORK DISTRIBUTION USING NOISE LOGGERS (PANGEEA, 2026)
Water losses in distribution networks represent a significant challenge for utilities worldwide, resulting in wasted resources, increased operational costs and infrastructure damage. These losses are classified into real losses (physical leaks in pipes, joints and fittings) and apparent losses (caused by measurement errors or unauthorized consumption). Real losses, in particular, require effective detection and mitigation strategies to improve network efficiency and sustainability. This pilot project in Piatra Neam aims to increase the efficiency of leak detection using advanced technology for recording and transmitting noise from distribution networks. The project involves installing noise loggers at strategic points, such as in valve chambers, within the distribution system. These devices continuously monitor/correlate noise from pipes, identifying potential leaks based on characteristic sound patterns. Data from the loggers is transmitted to a central platform, where algorithms filter out background noise and identify anomalies that indicate leaks. This real-time monitoring allows for early detection of leaks, reducing water losses and minimizing repair costs. Key objectives include evaluating the effectiveness of the noise loggers in a real-world setting, optimizing their placement for maximum coverage, and integrating the system with existing SCADA network management tools. Field tests involve correlation techniques to confirm leak locations and evaluate detection accuracy. Preliminary results suggest that the noise logger tools significantly improve detection time compared to traditional methods, especially in areas with pressure variations. This short paper demonstrates the potential of noise loggers as a scalable and cost-effective solution for proactive leak detection. The findings will contribute to more sustainable water management practices in Piatra Neamt and beyond.